"Was the Infant Born Alive?" A Review of Postmortem Techniques Used to Determine Live Birth In Cases of Suspected Neonaticide. Issue 4 (December 2018) - Phillips, Bianca; Ong, Beng Beng
The question of whether an infant was born alive has received much attention in the forensic literature. The volume of literature reflects the degree of controversy surrounding the techniques employed and their varied interpretation and utility. The majority of the investigation has been focused on the question "Has the infant breathed?" to determine if an infant was born alive by utilizing techniques that assess aeration of the lungs. However, caution must be employed when interpreting these techniques due to the well-recognized limitations in their interpretation, particularly in the presence of gaseous decomposition and/or resuscitation efforts. Although in some instances there may be irrefutable evidence that the infant was born alive, there is no single finding that can reliably be utilized to answer the question "Was the infant born alive?" in every case. Hence, the approach to postmortem investigation continues to include a wide range of observations, dissections, special techniques, and ancillary tests to assist the pathologist to form a considered opinion. There are a number of more recently described techniques which show great promise in assisting to answer this question including advanced imaging and immunohistochemical studies of the umbilical cord. It remains, though, that in many cases it is not possible to definitively answer this question and stillbirth should be assumed due to the potential legal implications of determining that an infant was born alive.